2020
DOI: 10.26353/j.itahort/2020.1.8599
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality performances of organic tomato as affected by genotype and industrial processing in southern Italy

Abstract: Identifying new tomato (Solanum lycopersicum L.) genotypes with improved technological performances is an important requisite for achieving high yield and quality of industrial produce. An open-field experiment was carried out in southern Italy in order to assess the effects of three elongated tomato hybrids oriented to ‘peeled’ chain (Max 14802, Massaro, Taylor) in terms of crop productivity and nutritional value. The hybrid Taylor showed the highest marketable yield due to the highest fruit number, whereas M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results for the soluble solids content in the current study are comparable with the results obtained for eight genotypes grown organically in Romania, varying from 4.10 to 5.60 • Brix [32]. In another study, De Sio et al [33] found higher values with 5.8 to 6.1 • Brix in tomatoes grown under organic management. Our pH values are comparable with those acquired by researchers from the southwest of Spain, who found that pH values ranged from 4.33 to 4.51 in 5 traditional tomato varieties grown organically in open air [34].…”
Section: Discussionsupporting
confidence: 88%
“…The results for the soluble solids content in the current study are comparable with the results obtained for eight genotypes grown organically in Romania, varying from 4.10 to 5.60 • Brix [32]. In another study, De Sio et al [33] found higher values with 5.8 to 6.1 • Brix in tomatoes grown under organic management. Our pH values are comparable with those acquired by researchers from the southwest of Spain, who found that pH values ranged from 4.33 to 4.51 in 5 traditional tomato varieties grown organically in open air [34].…”
Section: Discussionsupporting
confidence: 88%
“…In this area, tomato is one of the most important cultivated crops [25]. This crop's production relies on a wide range of growth practices connected with varied cropping sites (greenhouse or open field), fertiliser inputs (mineral or organic), and energetic requirements (electricity and fossil fuel) [26]. The growth season, which runs from May to August, is marked by high temperatures (sometimes above 40 • C) and little precipitation (180 mm, on average, between 1981 and 2010).…”
Section: Study Areamentioning
confidence: 99%